A WEB-DATABASE APPLICATION FOR BIOLOGICAL DATA MANAGEMENT OF FUNGI SPECIES - Emran, Nurul A. (2007)
Web-database technology has been extended in more advanced applications like biological sciences. The importance of developing universal-access database applications for biological sciences community is undeniable. The real challenge lies in the complex structure of biological data. It becomes the goal of biological data modelling to express biologists understanding of their knowledge and to support their biological discovery activities. A traditional data modelling method called relational data modeling is used for this purpose. This paper states the reason why this web-database application for fungi species is developed using relational data model, instead of an object-based model. The paper proves that relational modelling is capable to capture the semantics of fungus biological properties at the right abstraction level. This application is developed with data management and query capabilities for fungi database. The approach is evaluated against several current real-world database applications for biological data.